B45 TAU-positive nuclear indentations in P301S tauopathy mice. (13th September 2016) - Fernández-Nogales, Marta; Santos-Galindo, María; Merchan-Rubira, Jesús; Hoozemans, Jeroen; Rábano, Alberto; Ferrer, Isidro; Ávila, Jesús; Hernández, Félix; Lucas, José J
Abstract : Increased incidence of neuronal nuclear indentations is a well-known feature of the striatum of Huntington's disease (HD) brains and, in Alzheimer's disease (AD), neuronal nuclear indentations have recently been reported to correlate with neurotoxicity due to improper cytoskeletal/nucleoskeletal coupling. Initial detection of rod-shaped tau immunostaining in nuclei of cortical and striatal neurons of HD brains and in hippocampal neurons of early Braak stage AD led us to coin the term "tau nuclear rods (TNRs)". Although TNRs traverse nuclear space, they in fact occupy narrow cytoplasmic extensions that fill indentations of the nuclear envelope and we will here refer to this histological hallmark as Tau-immunopositve nuclear indentations (TNIs). We reasoned that TNI formation is likely secondary to tau alterations as TNI detection in HD correlates with an increase in total tau, particularly of the isoforms with four tubulin binding repeats (4R-tau). Here we analyse transgenic mice that overexpress human 4R-tau with a frontotemporal lobar degeneration-tau point mutation (P301S mice) to explore whether tau alteration is sufficient for TNI formation. Immunohistochemistry with various tau antibodies, immunoelectron microscopy and double tau-immunofluorescence/DAPI-nuclear counterstaining confirmed that excess 4R-tau in P301S mice is sufficient for the detection of abundant TNIs that fill nuclear indentations. Interestingly, this does not correlate with an increase in the number of nuclear indentations, thus suggesting that excess total tau or an isoform imbalance in favour of 4R-tau facilitates tau detection inside preexisting nuclear indentations but does not induce formation of the latter. In summary, here we demonstrate that tau alteration is sufficient for TNI detection and our results suggest that the neuropathological finding of TNIs becomes a possible indicator of increased total tau and/or increased 4R/3R-tau ratio in the affected neurons apart from being an efficient way to monitor pathology-associated nuclear indentations.